PROSPECTS FOR DEVELOPING PRIVATE CRIMINALISTIC DOCTRINES ON THE PERSONALITY OF A MINOR PARTICIPANT IN CRIMINAL PROCEEDINGS - ZAINULLIN Ruslan Ildarovich (Правовое государство: теория и практика, 2023)
The problems of enriching the theoretical basis of the science of criminalistics have always been very topical. All the more so if such doctrines (theories) are applied, and their results can be used in modern law enforcement practice. The purpose of this publication is to study the prospects for the formation of private criminalistic doctrines on the personality of a minor participant in criminal proceedings. Methods: empirical methods of comparison, description, interpretation; theoretical methods of formal and dialectical logic; specific scientific methods: legal-dogmatic and interpretation of legal norms. Results: the author identifies a list of current problems that require their theoretical justification and solution, determines the prospects for future scientific criminalistic research. The identification and resolution of the issues involved will enhance the focus of research in the field of private criminalistic doctrines.